1958
DOI: 10.1063/1.1723219
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering of Surfaces by Positive Ion Beams of Low Energy

Abstract: Silver, germanium, and germanium-silicon alloy surfaces have been bombarded with the inert gas ions Ne+, A+, Kr+, and Xe+, at energies between 30 and 400 ev. Primary beam intensities between one and ten μa/cm2 were obtained in an oscillating electron source of the Heil type. The secondary particles sputtered off, neutrals as well as positive and negative ions, were identified and recorded in a 180° mass spectrometer of 5.5-inch radius. They are partly background gases adsorbed on the surface, partly atoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

1965
1965
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 257 publications
(48 citation statements)
references
References 8 publications
0
45
0
3
Order By: Relevance
“…They found no evidence of a pressure effect on sputtering yields. At much lower energies (up to 400eV), Honig (1958) found that a bombardment ratio of between 0.2 and 2 was not sufficient to maintain a clean surface. Wolsky and Zdanuk (1961) bombarded Si with A+ ions of energy up to 800eV.…”
Section: Fig 23 Average Ejection Energies (E) For Atoms Ejected Inmentioning
confidence: 99%
See 4 more Smart Citations
“…They found no evidence of a pressure effect on sputtering yields. At much lower energies (up to 400eV), Honig (1958) found that a bombardment ratio of between 0.2 and 2 was not sufficient to maintain a clean surface. Wolsky and Zdanuk (1961) bombarded Si with A+ ions of energy up to 800eV.…”
Section: Fig 23 Average Ejection Energies (E) For Atoms Ejected Inmentioning
confidence: 99%
“…Hillocks were observed which were thought to be associated with the accumulation of mobile surface atoms at locally active centres on the amorphous surface layer. Honig (1958) attributed the presence of hillocks on (111) Ge and 0 (221) Ge-Si, which were several hundred A in height, to aggregates of C atoms which, because of their low sputtering yield, served to mask off parts of the surface which were left standing as hillocks. Meckel (1966) interpreted the presence of strange hillocks found on sputtered Ge surfaces as being due to small electrically insulating particles covering the surface.…”
Section: P-n Junction Devicesmentioning
confidence: 99%
See 3 more Smart Citations